Vyrai nusivylimo ekonomikose: tarp gero gyvenimo ir socialinės atskirties Men in the economies of disappointment: between good life and social exclusion - Indriliūnaitė, Rasa (Vytautas Magnus University, 2016)
Unemployed, homeless and imprisoned men analysed in this book experience risk of social exclusion that encompass the factors of labour market, masculinity, crime, poverty, social capital, social participation, consumption and emotional wellbeing. The authors of the study ask how these groups of men live their lives in Lithuania in which the social welfare is available only to a small fraction of society. In what ways do these men react to their situation and what survival strategies do they choose? The book also explores what it means to live in the economy of disappointment that contradicts normativity of happiness sustained by desperate optimism and attachment to the vision of good life. Each chapter of the book not only describes socially deprived men's lives but also reflects on the notions of social exclusion, masculinity, subjective wellbeing, good life, social networks, social welfare system and optimism.